2020
DOI: 10.3390/proteomes8020007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Reference Ranges of Total Serum Protein in Namibia: Clinical Implications

Abstract: A reference range is an essential part of clinical laboratory test interpretation and patient care. The levels of total serum protein (TSP) are measured in sera to assess nutritional, liver, and kidney disorders. This study determined the TSP reference range with respect to gender, age, and region in Namibia. A retrospective cross-sectional study was conducted to determine the TSP reference range among 78,477 healthy participants within the ages of less than one year to more than 65 years in 14 regions of Nami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The same conclusions stem from the analysis of the total protein (TP) values, which provide an estimation of the nutritional status and assist in diagnosing several pathological conditions associated with liver and kidney disease. 61,62 A reduction in total protein (albumin and globulin), not observed in this work, is an indicator of an impaired hepatocellular function. The results obtained for the serum urea, creatine and electrolyte Environmental Science: Nano Paper concentrations, analyzed as indices of renal function, 63 also suggest that BNC did not impact the normal renal function among all studied groups.…”
Section: Assessment Of the Systemic Toxicitymentioning
confidence: 55%
“…The same conclusions stem from the analysis of the total protein (TP) values, which provide an estimation of the nutritional status and assist in diagnosing several pathological conditions associated with liver and kidney disease. 61,62 A reduction in total protein (albumin and globulin), not observed in this work, is an indicator of an impaired hepatocellular function. The results obtained for the serum urea, creatine and electrolyte Environmental Science: Nano Paper concentrations, analyzed as indices of renal function, 63 also suggest that BNC did not impact the normal renal function among all studied groups.…”
Section: Assessment Of the Systemic Toxicitymentioning
confidence: 55%
“…Lower total protein may suggest liver disorders that inhibit albumin and globulin production, while hepatitis has been linked to higher total serum protein. 68 …”
Section: Discussionmentioning
confidence: 99%
“…Lower total protein may suggest liver disorders that inhibit albumin and globulin production, while hepatitis has been linked to higher total serum protein. 68 There are no toxicological studies directly examining sex differences in the relationship between neonicotinoids and liver function markers. An epidemiological study in China found no significant sex differences associated with the reporting of liver cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Total serum protein (TSP) was determined in each sample following the Biuret method (Henok et al, 2020) using the Randox Total Protein Test Kit (Randox Laboratories, Leeds, UK). Serum albumin concentration was determined following the bromocresol green method (Anonymous, 2020), using the Randox Albumin Test Kit (Randox Laboratories, Leeds, UK).…”
Section: Determination Of Biochemical Parametersmentioning
confidence: 99%